Effectiveness of the pre-Omicron COVID-19 vaccines against Omicron in reducing infection, hospitalization, severity, and mortality compared to Delta and other variants: A systematic review. Issue 1 (31st December 2023) - Paul, Pradipta; El-Naas, Ahmed; Hamad, Omar; Salameh, Mohammad A.; Mhaimeed, Nada; Laswi, Ibrahim; Abdelati, Ali A.; AlAnni, Jamal; Khanjar, Bushra; Al-Ali, Dana; Pillai, Krishnadev V.; Elshafeey, Abdallah; et al.
ABSTRACT: Despite widespread mass rollout programs, the rapid spread of the SARS-CoV-2 Omicron variant called into question the effectiveness of the existing vaccines against infection, hospitalization, severity, and mortality compared to previous variants. This systematic review summarizes and compares the effectiveness of the COVID-19 vaccines, with respect to the above outcomes in adults, children, and adolescents. A comprehensive literature search was undertaken on several databases. Only 51 studies met our inclusion criteria, revealing that the protection from primary vaccination against Omicron infection is inferior to protection against Delta and Alpha infections and wanes faster over time. However, mRNA vaccine boosters were reported to reestablish effectiveness, although to a lower extent against Omicron. Nonetheless, primary vaccination was shown to preserve strong protection against Omicron-associated hospitalization, severity, and death, even months after last dose. However, boosters provide more robust and longer-lasting protection against hospitalizations due to Omicron as compared to only primary series.